2021
DOI: 10.1177/1833358321991362
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting clinicians’ adherence to principles of diagnosis documentation: A concept mapping approach for improved decision-making

Abstract: Background: The quality of data in electronic health records (EHRs) depends on adherence of clinicians to principles of diagnosis documentation. Objective: A concept mapping (CM) approach was used to extract factors related to quality of clinicians’ documentation that govern EHR data quality. Method: Influential factors extracted from brainstorming sessions were sorted by individual participants, followed by a quantitative analysis using multidimensional scaling and cluster analysis to categorise sorted factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Some studies have proposed techniques for improving completeness, including developing fit-for-purpose user interfaces [ 68 , 96 , 97 ], standardizing documentation practices, [ 98 , 99 ], automating documentation [ 100 ], and performing quality control [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have proposed techniques for improving completeness, including developing fit-for-purpose user interfaces [ 68 , 96 , 97 ], standardizing documentation practices, [ 98 , 99 ], automating documentation [ 100 ], and performing quality control [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…For data to be considered complete, it needs to be captured at sufficient breadth and depth over time [12,18]. Some studies have proposed techniques for improving completeness, including developing fit-for-purpose user interfaces [68,96,97], standardizing documentation practices, [98,99], automating documentation [100], and performing quality control [99].…”
Section: Dq Dimension: Completenessmentioning
confidence: 99%
“…The importance of clinical documentation improvement was reported in other studies 18,39 . As such, we conducted a study using a concept mapping approach to extract factors affecting clinicians’ adherence to principles of diagnosis documentation from the viewpoint of physicians 40 . The extracted factors were classified into 7 clusters including: ‘knowledge about ICD and clinical coding,’ ‘need for facilitators and guidelines,’ ‘explain the importance of the issue and define responsibilities,’ ‘cooperation of other personnel,’ ‘codify legal requirements,’ ‘workload,’ and ‘clinical obstacles,’ as ranked by their importance.…”
Section: Discussionmentioning
confidence: 99%
“…18,39 As such, we conducted a study using a concept mapping approach to extract factors affecting clinicians' adherence to principles of diagnosis documentation from the viewpoint of physicians. 40 The extracted factors were classified into 7 clusters including:…”
Section: Discussionmentioning
confidence: 99%
“…Jebraeily et al (2023) found causes of clinical coding problems standing in the way of quality improvement fell into five groupings: policies, protocols and processes; individual factors; equipment and materials; working environment and management factors; and quality of clinical coding could be improved by hospital managers and health policymakers focusing on strategies and solutions that target these root causes. Hosseini et al (2022) argued that data quality enhancement requires collaboration between physicians, nurses, managers and developers of software, suggesting a concept mapping approach to meet this objective. Kilkenny et al (2023) recommended ongoing education for CCs to achieve high-quality coding and more accurate data.…”
Section: Virtual Special Issue On CDImentioning
confidence: 99%